What are they all doing in that restaurant? Perspectives on the use of theory of mind - Gabbatore, Ilaria; Bosco, Francesca M.; Tirassa, Maurizio (Frontiers in Psychology, 2024)
If “theory of mind” is conceived as reasoning in a strict sense, then it can be said to be useful only at certain times; however, this leaves the rest of social cognition hardly comprehensible. If “theory of mind” is used instead to refer to a mentalist ontology and the consequent awareness that we ourselves and the others function on mental states, then we need new approaches that explain the flow of social experience. To illustrate these points, we outline the general conceptual framework that underlies most empirical studies of theory of mind and discuss their pros and cons; then, we discuss the Theory of Mind Assessment Scale, a tool developed to investigate the complexity of theory of mind, which adopts a different perspective and has been successfully tested on numerous populations.